Minocycline Attenuates Stress-Induced Behavioral Changes via Its Anti-inflammatory Effects in an Animal Model of Post-traumatic Stress Disorder - Wang, Wei; Wang, Rui; Xu, Jingjing; Qin, Xiaqing; Jiang, Hong; Khalid, Arslan; Liu, Dexiang; Pan, Fang; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Psychiatry, 2018)
Accumulating evidences have suggested that anxiety-like behaviour and impairment of learning and memory are key symptoms of post-traumatic stress disorder (PTSD), and pharmacological treatment can ameliorate anxiety and cognitive impairments. Recent studies have shown that minocycline exhibits anxiolytic effects. The aims of the present study were to determine whether minocycline administration would alter anxiety-like behaviour and cognitive deficits induced by inescapable foot shock (IFS) and to explore the underlying mechanisms. Male Wistar rats were exposed to the IFS protocol for a period of six days to induce PTSD. The PTSD-like behaviour was tested using the open field test, elevated plus maze test and Morris water maze test. The effects of minocycline on pro-inflammatory cytokines, activation of microglia and NF-κB in the PFC and hippocampus were also examined. Treatment with minocycline significantly reversed the IFS induced behavioural and cognitive parameters (impaired learning and memory function) in stressed rats. Additionally, IFS was able to increase pro-inflammatory cytokines, activate microglia and enhance NF-κB levels, while minocycline significantly reversed these alterations. Taken together, our results suggest that the anxiolytic effect of minocycline is related to its ability to decrease the levels of pro-inflammatory cytokines and inhibit activation of microglia and NF-κB in the PFC and hippocampus.